Program Maghrib Mengaji Dalam Upaya Penuntasan Buta Aksara Al-Qur’an di Desa Dayang Suri - -, M. FIkri; Mahdini, Dwi; Ariansyah, Wahyu; Silvia, Reni; Arifin, Zaenal; Kurnia, Wirza; Nabila, Mutia; Lina, Ejma Rukma; Chania, Melsa; Hidayah, Mitahul; et al. (Jurnal Pengabdian Masyarakat dan Penerapan Ilmu Pengetahuan, 2025)
The Maghrib Mengaji Program is a community service initiative aimed at eradicating illiteracy in reading the Qur'an in Dayang Suri Village, Bungaraya Subdistrict, Siak Regency. This initiative was prompted by the condition of the village children, who, despite having reached an advanced level in the Iqra’ program, still struggled with correctly pronouncing the Arabic alphabet. The program was conducted over two weeks using a participatory approach, actively involving the community from problem identification to activity implementation. Learning methods included talaqqi (group recitation) and remedial approaches, with reading levels adjusted to strengthen foundational Quranic reading skills. The results showed a significant improvement in the quality of participants' reading, as well as growing enthusiasm among the community in supporting the activity. The program successfully revived the tradition of post-Maghrib Quran recitation as part of spiritual development at the village level. The success of this program demonstrates that an educational and community-based approach can be an effective solution in addressing Quranic illiteracy in a sustainable manner. Maghrib Mengaji, Illiterate in the Qur'an, Community Service